Effects of Knowledge Management & Concurrent Engineering on NPD Performance - Ng, Poh Kiat; Jee, Kian Siong (Journal of Knowledge Management Practice, 2013)
The progressively increasing customer awareness of quality raises the demand level of new product development (NPD) processes in manufacturing firms. As such, manufacturing firms of today require cutting-edge strategies, innovation and management skills to improve their level of NPD performance. This research aims to explore the effects of knowledge management and concurrent engineering on NPD performance. A total of 150 surveys were collected back from several Malaysian manufacturing firms and analyzed using reliability, correlations and multiple linear regression analyses. The results revealed that concurrent engineering has a higher influence over NPD performance compared to knowledge management. However, the combined effects of both concurrent engineering and knowledge management on NPD performance were found to be significant. According to the model, the significance of knowledge management is not to be ignored. Nevertheless, the combined practice of concurrent engineering and knowledge management is likely to be a dominant catalyst for improved NPD in most Malaysian manufacturing firms.